Enhancing Learning Through 3-D Virtual Environments - Champion, Erik (IGI Global, 2008)
We cannot begrudge students their envy in looking at popular films and computer games as major contenders for their spare time. While we as teachers could attempt to fight the popularity of games, I suggest a more useful endeavor would be to attempt to understand both the temptation of games, and to explore whether we could learn from them, in order to engage students and to educate them at the same time. There are still few applicable theories and successful case studies on how we could do this using virtual environments and associated technology (referred to by some as virtual reality, or VR). To help answer the question of “but what can we do about it,” I will outline several simplified theories of cultural learning based on interaction, and the experience I gained from employing them in two different virtual environment projects.